Effects of Anaplasma phagocytophila on NADPH Oxidase Components in Human Neutrophils and HL-60 Cells - Mott, Jason (American Society for Microbiology, 2002)
The human granulocytic ehrlichiosis agent, Anaplasma phagocytophila, resides and multiplies exclusively in cytoplasmic vacuoles of granulocytes. A. phagocytophila rapidly inhibits the superoxide anion (O(2)(−)) generation by human neutrophils in response to various stimuli. To determine the inhibitory mechanism, the influence of A. phagocytophila on protein levels and localization of components of the NADPH oxidase were examined. A. phagocytophila decreased levels of p22(phox), but not gp91(phox), p47(phox), p67(phox), or P40(phox) reactive with each component-specific antibody in human peripheral blood neutrophils and HL-60 cells. Double immunofluorescence labeling revealed that p47(phox), p67(phox), Rac2, and p22(phox) did not colocalize with A. phagocytophila inclusions in neutrophils or HL-60 cells, and p22(phox) levels were also reduced. A. phagocytophila did not prevent either membrane translocation of cytoplasmic p47(phox) and p67(phox) or phosphorylation of p47(phox) upon stimulation by phorbol myristate acetate. The inhibitory signals for O(2)(−) generation was independent of several signals required for A. phagocytophila internalization. These results suggest that rapid alteration in p22(phox) induced by binding of A. phagocytophila to neutrophils is involved in the inhibition of O(2)(−) generation. Absence of colocalization of NADPH oxidase components with the inclusion further protects A. phagocytophila from oxidative damage.